2007
DOI: 10.1152/ajpendo.00521.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of apelin and its receptor in the anterior pituitary: evidence for a direct stimulatory action of apelin on ACTH release

Abstract: Reaux-Le Goazigo A, Alvear-Perez R, Zizzari P, Epelbaum J, Bluet-Pajot MT, Llorens-Cortes C. Cellular localization of apelin and its receptor in the anterior pituitary: evidence for a direct stimulatory action of apelin on ACTH release. Am J Physiol Endocrinol Metab 292: E7-E15, 2007. First published August 8, 2006; doi:10.1152/ajpendo.00521.2005.-Apelin is a bioactive peptide recently identified as the endogenous ligand of the human orphan G protein-coupled receptor APJ. The presence of apelin-immunoreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 44 publications
(71 reference statements)
2
44
2
4
Order By: Relevance
“…Apelin may potentially stimulate the secretion of ACTH either directly at the level of the pituitary corticotroph or via an indirect action on the hypothalamus involving the release of both VP and CRH. Consistent with the expression of apelin and APJ in anterior pituitary corticotrophs, administration of apelin-17 directly increases the release of ACTH, while also augmenting K C -stimulated ACTH release, in an ex vivo perfusion system of anterior pituitary glands, suggesting possible autocrine or paracrine functions for apelin in this tissue (Reaux-Le Goazigo et al 2007). Central administration of (Pyr 1 )apelin-13 in rats also increases plasma ACTH and CORT levels while decreasing prolactin, luteinising hormone and follicle-stimulating hormone levels (Taheri et al 2002).…”
Section: Apelin/apj and The Neuroendocrine Response To Stresssupporting
confidence: 55%
See 1 more Smart Citation
“…Apelin may potentially stimulate the secretion of ACTH either directly at the level of the pituitary corticotroph or via an indirect action on the hypothalamus involving the release of both VP and CRH. Consistent with the expression of apelin and APJ in anterior pituitary corticotrophs, administration of apelin-17 directly increases the release of ACTH, while also augmenting K C -stimulated ACTH release, in an ex vivo perfusion system of anterior pituitary glands, suggesting possible autocrine or paracrine functions for apelin in this tissue (Reaux-Le Goazigo et al 2007). Central administration of (Pyr 1 )apelin-13 in rats also increases plasma ACTH and CORT levels while decreasing prolactin, luteinising hormone and follicle-stimulating hormone levels (Taheri et al 2002).…”
Section: Apelin/apj and The Neuroendocrine Response To Stresssupporting
confidence: 55%
“…Further studies focusing on the PVN, SON, median eminence and dorsolateral accessory magnocellular nucleus have shown strong labelling for apelin and co-localisation with VP (Brailoiu et al 2002) and with oxytocin (OT; Brailoiu et al 2002) in the SON and PVN. Apelin is also co-localised with adrenocorticotrophin (ACTH) in corticotrophs and to a lesser extent with growth hormone in somatotropes in the anterior pituitary (Reaux-Le Goazigo et al 2007).…”
Section: Rat Distributionmentioning
confidence: 99%
“…6 Immunoactivity of apelin and its receptor have been also found in the brain, including hypothalamus. 7 This is consistent with a potential role of apelin in the control of pituitary hormone release, 8 body fluid equilibrium, and drinking behavior. 9 It has been shown that apelin expression is increased by tumor necrosis factor α (TNF-α) 10 and hypoxia-inducible factor 1-α 11 (HIF-1α) and decreased by aldosterone.…”
Section: Methodssupporting
confidence: 70%
“…Apelin receptor antisense and sense cRNA probes were synthesized by in vitro transcription as previously described (20,58). Sections were hybridized with the apelin receptor antisense and sense cRNA probes as previously described (20,63).…”
Section: Double Labeling For Apelin Receptor Mrna and Pomc By A Combimentioning
confidence: 99%